OCT evaluation of orthodontic surface sealants: a 12-month follow-up randomized clinical trial - Şen, Sinan; Erber, Ralf; Orhan, Gül; Zingler, Sebastian; Lux, Christopher J. (Clinical oral investigations, 2021)
The aim of this single-center randomized controlled trial (NCT03753256) was to assess orthodontic surface sealant layer thickness and integrity in vivo during a 12-month follow-up by optical coherence tomography (OCT).
Published online: 13 August 2020
Gesehen am 04.10.2021